Single-grain apatite (U-Th)/He (AHe) analytical results and sample ages (Table S1) - Sarah Falkowski; Todd A Ehlers (PANGAEA, 2023)
This dataset (Table S1) contains a total of 163 single-grain analytical data of apatite (U-Th)/He (AHe) measurements from 49 of the newly collected bedrock samples. Furthermore, the data table contains weighted mean AHe ages for reset samples. Data were acquired between 2018 and 2020 at the University of Tübingen, Germany, using standard heavy mineral separation techniques to obtain apatite concentrates, a Leica binocular for apatite selection, a Patterson helium line for single-grain helium measurements, and a Thermo Fisher Scientific iCAP Qc and Agilent 7900 ICP-MS for uranium, thorium, and samarium measurements via isotope dilution inductively coupled plasma mass spectrometry.
In: Falkowski, S; Ehlers, TA (2023): Low-temperature thermochronometric data (AHe, AFT, ZHe, ZFT) from three bedrock sample transects across the eastern Central Andes, southern Peru [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.955437